EFL students' Perspectives on Learning Grammar through English Conversation - Febriyanti, Rizki Ika; Izdihar, Fairuz Nadhifah; Hairulla, Monera A. Salic (Universitas Muhammadiyah Semarang, 2024)
This research aims to find out the EFL students' point of view on the importance of using grammar in a conversation. The research method used is descriptive qualitative. The data collection technique uses semi-structured interviews to explore EFL students' points of view. The subjects of this research were thirty students who are enrolled in the second-year English department class at Muhammadiyah University Semarang. Based on the interviews that have been conducted, the known results are that the majority of EFL students have the perspective that the use of grammar in speaking English is very important. EFL students recognize the importance of using useful grammar to understand meaning when speaking English. For them, being able to speak with perfect grammar is proof of someone's success in learning English.Keywords: EFL students, perspective, grammar